Pengaruh Harga dan Kualitas Pelayanan Terhadap Penjualan pada Bengkel Hendri Motor dan Sparepart Cabang Ciputat - Wahyu Nugroho, Arif; Hanny, Rissa (Teewan Journal Solutions, 2025)
This research aims to determine the effect of price and service quality on sales at the Ciputat branch of the Hendri Motor and Spare Parts workshop. The method used is a quantitative approach. The population in this research consists of 3,600 customers of Hendri Motor and Spare Parts workshop. Data processing was assisted by the SPSS version 26 application. The sampling technique used was nonprobability sampling, with the sample size determined using the Slovin formula, resulting in a sample of 100 respondents. The data analysis methods used include instrument tests (validity and reliability tests), classical assumption tests (normality, multicollinearity, autocorrelation, and heteroscedasticity tests), multiple linear regression analysis, correlation coefficients, hypothesis testing (partial t-test and simultaneous F-test), and determination coefficient tests. The results of this research indicate that both price and service quality have a positive and significant effect on sales. Price has a significant influence with a t-value of 2.070 > t-table 1.661 and a significance value of 0.041 < 0.05. Service quality also has a significant influence with a t-value of 2.283 > t-table 1.661 and a significance value of 0.027 < 0.05. Simultaneously, price and service quality significantly affect sales with an F-value of 4.882 > F-table 3.09 and a significance value of 0.000 < 0.05.